(untitled) - Gammie, John G. (Minneapolis, U.S.A, 1989)
Gammie's careful study represents an important theological resource for our own work. The holiness of God is clearly not simply an antiquarian concern. Our uneasiness with such a theological emphasis is surely reflective of the urgency of that very assertion. God's holiness marked by majesty for God's self and by passion for the justice of the world takes on power and urgency in the face of our own life issues. The holiness of God is urgent in the face of profanation, which empties life of larger passion and dignity. The holiness of God is urgent in the face of pervasive brutality, which trivializes God's purpose and abuses God's world. The holiness of God is urgent in the face of the growing authority of technique, which diminishes mystery that keeps life open. Israel struggles to speak aright about God. From the Editor's Foreword by Walter Brueggemann
Keywords: Bible -- A.T -- Theologie